DHA Suppresses Hepatic Lipid Accumulation via Cyclin D1 in Zebrafish - Ding, Qianwen; Hao, Qiang; Zhang, Qingshuang; Yang, Yalin; Olsen, Rolf Erik; Ringø, Einar; Ran, Chao; Zhang, Zhen; Zhou, Zhigang (Frontiers in Nutrition, 2022)
With the widespread use of high-fat diets (HFDs) in aquaculture, fatty livers are frequently observed in many fish species. The aim of this study was to investigate if docosahexaenoic acid (DHA) could be used to reduce the fatty liver in zebrafish generated by a 16% soybean oil-HFD over 2 weeks of feeding. The DHA was added to iso-lipidic HFD at 0.5, 1.0 and 2.0% of diet. Supplementation of DHA reduced growth and feed efficiency in a dose dependent manner being lowest in the HFDHA2.0 group. Hepatic triglyceride (TG) in zebrafish fed 0.5% DHA-supplemented HFD (HFDHA0.5) was significantly lower than in the HFD control. Transcriptional analyses of hepatic genes showed that lipid synthesis was reduced, while fatty acid β-oxidation was increased in the HFDHA0.5 group. Furthermore, the expression of Cyclin D1 in liver of zebrafish fed HFDHA0.5 was significantly reduced compared to that in fish fed HFD. In zebrafish liver cells, Cyclin D1 knockdown and blocking of Cyclin D1-CDK4 signal led to inhibited lipid biosynthesis and elevated lipid β-oxidation. Besides, DHA-supplemented diet resulted in a rich of Proteobacteria and Actinobacteriota in gut microbiota, which promoted lipid β-oxidation but did not alter the expression of Cyclin D1 in germ-free zebrafish model. In conclusion, DHA not only inhibits hepatic lipid synthesis and promotes lipid β-oxidation via Cyclin D1 inhibition, but also facilitates lipid β-oxidation via gut microbiota. This study reveals the lipid-lowering effects of DHA and highlights the importance of fatty acid composition when formulating fish HFD.